Pengaruh Siswa Pesantren dan Non Pesantren Terhadap Hasil Belajar Siswa Mata Pelajaran Pendidikan Agama Islam Kelas VIII SMP As Salafiyah Krangkeng - Nuni Oktaviani; Ratu Anggraeni (Khulasah : Islamic Studies Journal, 2020)
Education can be defined as a process using certain methods so that people gain knowledge, understanding and behave in accordance with their needs. In every educational institution there must be teaching and learning process activities between teachers and students and student success can be seen from the learning outcomes in their achievements. Learning outcomes are results achieved by students, but can not only be assessed academically, but also seen from changes in students when interacting with their environment. The main problem in this research is how the learning outcomes of Islamic boarding school students and non-Islamic boarding school students differ in the Islamic Religious Education class VIII SMP As Salafiyah Krangkeng subjects. This research is a type of quantitative research, the population in this research is all 30 class VIII students, while the sample in this research is 12 Islamic boarding school students and 12 non-Islamic boarding school students. The type of data in this research is quantitative, bivariant and qualitative comparison. The quantitative data uses total student data and report card grades, while the qualitative data is the result of direct observations and interviews with the school and students. Factors that influence learning outcomes, Islamic boarding school students study more regularly and have special time to repeat lessons, while non-Islamic boarding school students are lazy to repeat lessons and only study when they have assignments from school. From the results of the analysis, the mean learning outcomes for Islamic boarding school students are 85 and non-Islamic boarding school students are 82.3 and based on analysis which states that the calculated t is greater than the t table at the 5% significance level, namely 4.82 > 1.717.